The future of political science? the politics and management of the academic expectations gap: evidence from the UK. Issue 4 (December 2018) - Flinders, Matthew
Abstract Political science has for some time been afflicted with an existential and empirical angst concerning impact and relevance. This is by no means a new or unique disciplinary pathology, but it is one that has intensified in recent years. The reasons for this intensification have been explored in a burgeoning literature on 'the tyranny of impact'. The central argument of this article is that a focus on the 'relevance gap' within political science, and vis-à-vis the social sciences more generally, risks failing to comprehend the emergence of a far broader and multifaceted 'expectations gap'. The core argument and contribution of this article is that the future of political science will depend on the politics and management of the 'expectations gap' that has emerged. Put slightly differently, the study of politics needs to have a sharper grasp of the politics of its own discipline and the importance of framing, positioning, connectingvis -à -vis the broader social context.